The impact of stimulus arousal level on emotion regulation effectiveness in borderline personality disorder. (30th July 2016) - Fitzpatrick, Skye; Kuo, Janice R.
Abstract: Basic emotion theory suggests that the effectiveness of different emotion regulation strategies vary with the intensity of the emotionally-salient stimulus. Although findings from studies using healthy samples are concordant with what is proposed by theory, it is unclear whether these relationships hold true among individuals with borderline personality disorder (BPD). Twenty-five individuals with BPD and 30 HCs were exposed to negative images of varying levels of emotional arousal and were instructed to either react as they normally would, distract, or use mindful awareness. Self-reported negativity ratings, heart rate, and skin conductance level (SCL) were monitored throughout. SCL data indicated that increases in image arousal resulted in larger reductions in SCL when distracting but not when implementing mindful awareness. Self-report data suggested that, in HCs, the effectiveness of mindful awareness decreased to a greater extent than distraction when image arousal increased. These findings are consistent with basic emotion research and suggest that some forms of emotion regulation (distraction) are more suited to high emotion arousal contexts than others (mindful awareness) and that, compared with HCs, individuals with BPD may be more resilient to the deteriorating effectiveness of mindful awareness with respect to increasing emotional arousal. Highlights: Studied emotion regulation effectiveness in BPD and HC as a function of stimulus arousal levels. Distraction may be more suited to high stimulus arousal conditions. In HCs mindfulness was less effective than distraction when stimulus arousal increased. BPD group did not exhibit differential effectiveness between strategies when stimulus arousal increased. Emotion regulation in BPD may be more resilient to high stimulus arousal than HC.